P-selectin glycoprotein ligand-1 and cardiovascular diseases: from a general perspective to an HIV infection context - Zaongo, Silvere D.; Song, Yuxia; Chen, Yaokai (Frontiers in Cardiovascular Medicine, 2025)
Globally, cardiovascular diseases (CVDs) are a leading cause of death as they are responsible for the loss of at least 17 million lives annually. It has been established that the pathogenesis of CVDs is strongly associated both with inflammation as well as with inflammatory markers (proteins, cytokines, amongst others). In this perspective, the role of one of these proinflammatory proteins, referred to as P-selectin glycoprotein ligand (PSGL)-1, is of particular interest. Indeed, contemporary evidence points to the fact that P-selectin glycoprotein ligand (PSGL)-1 plays a critical role in the development of CVDs via its interactions with P-selectin, L-selectin, and/or E-selectin. However, due to the dearth of published contemporary research concerning PSGL-1 expression in people living with HIV (PLWH), it remains challenging to comprehensively investigate this area of study, although potential clues exist in the literature which may serve as potential directions for future investigations. Hence, in the first part of this article, a scoping review of the literature regarding the role of PSGL-1 in the development of CVDs is provided. Then, in the second part, observations concerning PSGL-1 expression in PLWH receiving ART are presented and interpreted. Through this work, we hope that increased attention will be directed towards the screening of PSGL-1 expression, which we believe may serve as a reliable biomarker to predict the presence and evolution of CVDs in PLWH.